Association between second-hand smoke exposure and lung cancer risk in never-smokers: a systematic review and meta-analysis - Irene Possenti; Marco Romelli; Giulia Carreras; Annalisa Biffi; Vincenzo Bagnardi; Claudia Specchia; Silvano Gallus; Alessandra Lugo (European Respiratory Review)
Background Lung cancer ranks as the leading cause of cancer-related deaths worldwide. There is evidence that second-hand smoke (SHS) exposure is a risk factor for the development of lung cancer in never-smokers. This systematic review and meta-analysis aims to provide the most accurate quantification of the association between SHS exposure and lung cancer risk in never-smokers. Materials and methods Through the use of an innovative method to identify original publications, we conducted a systematic review of the literature, with corresponding meta-analysis, of all epidemiological studies evaluating the association between SHS exposure and lung cancer risk among never-smokers, published up to May 2023. Pooled relative risks were obtained using random-effects models. Dose–response relationships were derived using log-linear functions or cubic splines. Results Out of 126 identified eligible studies, 97 original articles were included in the meta-analysis. The pooled relative risk for lung cancer for overall exposure to SHS was 1.24 (95% CI 1.16–1.32, number of articles, n=82). Setting-specific relative risks were 1.20 (95% CI 1.12–1.28, n=67) for SHS exposure at home, 1.38 (95% CI 1.28–1.62, n=30) at a workplace, 1.37 (95% CI 1.22–1.53, n=28) at home or a workplace and 1.27 (95% CI 1.11–1.44, n=24) in nonspecified settings. The risk of lung cancer significantly increased with the duration, intensity and pack-years of SHS exposure. Conclusions This meta-analysis shows that exposure to SHS increases by more than 20% the risk of lung cancer among never-smokers, providing definitive evidence of the association between SHS exposure and lung cancer risk.